PERAN PEMERINTAH DAERAH DALAM MENINGKATKAN UMK BURUH ROKOK PR. NOJORONO DI KABUPATEN KUDUS - Arief Baktiar; Achmad Taufiq; Suwanto Adhi (Journal of Politic and Government Studies, 2016)
ABSTRACTThe purpose of this research is to 1 ) to examine the role of the local government of kabupaten Kudus in order to increase labor umk in cigarette Kudus; and 2 ) to examine obstacles that experienced by the local government to efforts to improve labor umk in cigarette kabupaten Kudus .This research incline to qualitative descriptive with the subject of this study is 1 ) the head of remuneration board kabupaten Kudus; 2 ) regional secretary kabupaten Kudus; 3 ) the head of government of the district government Kudus; and 4 ) one of the entrepreneurs cigarette factory in kabupaten KudusThe results of the study shows that the involvement of the local government of kabupaten Kudus in order to increase ukm factory workers cigarette is nothing to creating balance industrial relations in the regions .In the industrial relations , i.e. the system relationships formed between actors in production process goods and / or services that consists of elements entrepreneurs , workers and the government based on values pancasila and the constitution of the republic of indonesia 1945 .In setting minimum wage was supposed to the interests of both employers and employees / laborers equally shelter fair .For workers / laborers really need wages appropriate in order to satisfy their daily needs so that can be achieved well-being , but for the company also need to get insurance when it has raise the minimum wage not being disturb the development and productivity company especially for medium-sized companies and smallThe result of the observation on the process discussion minimum wage in wage council the provincial level shows is that all the process that runs apparently place in a democratic and in accordance with governance work wage council .Every element of the joined in wage council have equal opportunities in express their opinions .Aspirations cigarette workers in kabupaten holy previously was stated by the local government of kabupaten holy , potentially have problem when they came in talks discussion at the wage council province , so that the role of the local government of kabupaten holy be termarjinalisasiTransparency entrepreneurs about the ability his company indispensable .If workers know the companies condition , so demands increase of wage adapted to the state of company .In addition , the workers have to can provide an incentive that is favorable to company , for example through increased productivity .Increase of wage who was not in balance to increased productivity actually make competitiveness to grow weak and injurious laborers because will give chances reductions in force .That awareness must be built by both parties in order to have synergistic relations between businessmen and workersKata kunci : The role of the district government holy, umk laborers cigarette